2017
DOI: 10.1002/oby.21832
|View full text |Cite
|
Sign up to set email alerts
|

Omentin treatment of epicardial fat improves its anti‐inflammatory activity and paracrine benefit on smooth muscle cells

Abstract: Exogenous omentin might support a cardioprotective role through its effect on EAT regarding glucose uptake, anti-inflammatory response, and its paracrine role on smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the expression level of omentin was decreased in CAD patients (412). Importantly, it was suggested that exogenous omentin supplementation might support a cardioprotective role through its anti-inflammatory effect on EpiCAT (413). Increased levels of resistin in EpiCAT were also reported in patients with advanced coronary atherosclerosis and patients with acute coronary syndrome (414,415).…”
Section: Epicardial Adipose Tissuementioning
confidence: 98%
“…Furthermore, the expression level of omentin was decreased in CAD patients (412). Importantly, it was suggested that exogenous omentin supplementation might support a cardioprotective role through its anti-inflammatory effect on EpiCAT (413). Increased levels of resistin in EpiCAT were also reported in patients with advanced coronary atherosclerosis and patients with acute coronary syndrome (414,415).…”
Section: Epicardial Adipose Tissuementioning
confidence: 98%
“…In humans, an inverse correlation between omentin levels and IR is seen, both at the protein and mRNA levels [ 277 , 279 , 280 ]. Additional studies show that omentin has anti-inflammatory properties, diminishes cytokine expression [ 281 , 282 ], and is negatively associated with systemic inflammatory markers such as TNF and IL-6 [ 283 ].…”
Section: T2dm Outcomes/complications: Cardiovascular Riskmentioning
confidence: 99%
“…Omentin-1 is known to have key roles in the maintenance of body metabolism and insulin sensitivity, and has anti-inflammatory, anti-atherosclerotic, and cardiovascular-protective effects via AMP-activated protein kinase/Akt/NF-κB/mitogen-activated protein kinase (ERK, JNK, and p. 38) signaling (33). In cultured human vascular cells, exogenous omentin promoted glucose uptake, and improved the insulin activity and anti-inflammatory response (174).…”
Section: Omentinmentioning
confidence: 99%